Detection of Anti-Cardiolipin and Anti-β2glycoprotein I Antibodies Differs between Platforms without Influence on Association with Clinical Symptoms - Chayoua, Walid; Kelchtermans, Hilde; Moore, Gary W.; Gris, Jean-Christophe; Musial, Jacek; Wahl, Denis; Zuily, Stéphane; Gianniello, Francesca; Fontana, Pierre; Remijn, Jasper; Urbanus, Rolf T.; de Laat, Bas; Devreese, Katrien M. J. (Thrombosis and Haemostasis, 2019)
Background The anti-phospholipid syndrome (APS) is characterized by thrombosis and/or pregnancy morbidity with persistent presence of anti-phospholipid antibodies (aPL). Laboratory criteria include aPL detection by coagulation tests for lupus anticoagulant (LAC) or solid phase assays measuring anti-β2 glycoprotein I (aβ2GPI) or anti-cardiolipin (aCL) immunoglobulin (Ig) G/IgM antibodies. External quality control programs illustrate that commercially available aPL assays produce variable results.Objective We aimed to investigate the agreement and diagnostic accuracy of solid phase assays.Materials and Methods In this multi-centre study, 1,168 patient samples were tested on one site for aCL and aβ2GPI IgG/IgM antibodies by four solid phase test systems. Samples included APS patients, controls and monoclonal antibodies (MoAB) against different epitopes of β2GPI. LAC was determined by the local centre.Results aCL IgM assays resulted in the most discrepancies (60%), while aCL IgG and aβ2GPI IgM assays resulted in lower discrepancies (36%), suggesting better agreement. Discrepant samples displayed lower median aPL titers. Dependent on the solid phase test system, odds ratios (ORs) for thrombosis and pregnancy morbidity ranged from 1.98 to 2.56 and 3.42 to 4.78, respectively. Three platforms showed lower sensitivity for MoAB directed against the glycine (Gly) 40-arginine (Arg) 43 epitope of domain I of β2GPI.Conclusion Poor agreement was observed between different commercially available aCL and aβ2GPI IgG/IgM assays, hampering uniformity in the identification of aPL-positive patients. Clinical association was globally concordant between solid phase test systems considering results of the four aPL together. An assay sensitive in detecting the MoAB against Gly40-Arg43 of domain I of β2GPI reached the highest OR for thrombosis.
Keywords: solid phase assays; anti-cardiolipin; β2 glycoprotein I; epitope; thrombosis